Pendampingan Pengoperasian Aplikasi Monbela Di TPQ Al Hidayah Semanggi - Agustina Srirahayu; Muhammad Ali Mashar (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
This service is carried out as a mentoring activity for parents / students and teachers to be able to operate Monbela (Monitoring Al-Quran Learning Outcomes) so that student learning outcomes at TPQ Al Hidayah Semanggi can be monitored periodically. The ongoing process for reporting learning outcomes encountered obstacles in the delivery of results, due to the loss of student learning record books and difficult to read handwritten notes from other teachers. The method of implementing the service includes the pre-training stage with direct observation to prepare administration and correspondence before carrying out activities. The next stage is operational assistance, the implementation of mentoring uses a demo application simulation model, then the evaluation stage is to determine the results of the implementation of activities. Adequate facilities and facilities at TPQ Al Hidayah Se-manggi have not been maximized for the benefit of the process of delivering student learning outcomes. Therefore, the activities of assisting the operation of the Mondela application are deemed important. The Monbela application can be used by 3 sides of access rights, the first is the administrator, teacher and student / parent. Administrators can access it via the website, while teachers and parents / students use smartphones. The community service activities went well, the participants who followed were 3 teachers and 15 parents / students. There are 3 access rights from the Monbela application from the access of mobile-based teachers and parents / students who can process student assessment data and student attendance in real time according to the implementation of activities. From access, parents / students can receive notification reminders on the Monbela application 20 minutes before activities at TPQ take place. In addition, reporting on student learning outcomes in TPQ can be monitored by parents in real time so that parents can get information about the progress of the Al-Quran learning process.